A meta-analysis on the relation of empathy and utilitarian moral response - Tan, Ler Theng (2017)
Research on the relation of empathy and utilitarian moral response has been developing in the last decade but findings have been inconsistent. Additionally, while empirical research suggests that empathy is differentially related to utilitarian moral response on a spectrum of participant and study variables, a systematic synthesis of the current studies has yet to be conducted. Therefore, the present meta-analysis examined the relationship between empathy and utilitarian moral response, as well as possible moderation effects using 6,349 participants from a total of 20 studies. Overall, a significant negative correlation was found between empathy and utilitarian moral response. In addition, moderation effects were found for (a) researchers’ measurement of moral response (i.e., binary alternative, Likert scale); (b) measurement of empathy (i.e., whether empathy was directly measured and the component of empathy measured); (c) conceptualisation of moral dilemmas (i.e., use of personal force and benefit recipient in dilemmas); (d) research settings (i.e., laboratory, non-laboratory); and (e) age of participants. No significant moderation effects were found for researchers’ conceptualisation of moral response (i.e., judgment, choice) and gender. The limitations of current research and implications for future research are also discussed.